The heart-break of social rejection versus the brain wave of social acceptance - van der Veen, Frederik M. (Oxford University Press, 2014)
The effect of social rejection on cardiac and brain responses was examined in a study in which participants had to decide on the basis of pictures of virtual peers whether these peers would like them or not. Physiological and behavioral responses to expected and unexpected acceptance and rejection were compared. It was found that participants expected that about 50% of the virtual judges gave them a positive judgment. Cardiac deceleration was strongest for unexpected social rejection. In contrast, the brain response was strongest to expected acceptance and was characterized by a positive deflection peaking around 325 ms following stimulus onset and the observed difference was maximal at fronto-central positions. The cardiac and electro-cortical responses were not related. It is hypothesized that these differential response patterns might be related to earlier described differential involvement of the dorsal and ventral portion of the anterior cingulate cortex.